Uji Aktivitas Antibakteri Ekstrak Etanol Pelepah Tanaman Pisang Ambon (Musa Paradisiaca) Terhadap Bakteri Escherichia Coli Atcc 11229 Dan Staphylococcus Aureus Atcc 6538 Secara In Vitro - Alafiah, Dewi Tuti; , dr. M. Amin Romas, DSMK; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background : Banana sheaths contain chemical compounds such as saponins , tannins and flavonoids . These compounds work in the field of medicine . While the banana sap contains saponins , anthraquinones and quinones which is antibacterial Objective : To determine the antibacterial activity of ethanol extract of the stem of banana sheaths ( Musa paradisiaca ) against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 11229 in vitro . Methods : using the laboratory experimental research design with post test only control group design method. The subjet of the research were etanol extract of the stem of banana plant. Extract would be tested with antibacterial activity against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 11229 using wells method with a concentration of 5% b/v, 10% b/v, 20% b/v, 40% b/v, 60% b/v, 80% b/v. To analyze the data used Kruskal-Wallis non Parametri and Mann-Whitney test Results : Staphylococcus aureus inhibitory zone formed from concentration 40 % , 60 % and 80 % % with an average diameter of each resistance zone 8 mm , 10 mm and 13 mm. Statistically it has significant antibacterial power with p = 0,000 (p<005) but less effective compared with positive control. While in Escherichia coli has no antibacterial effect at all concentration. Conclusion : The ethanol extract of banana sheaths has antibacterial activity against Staphylococcus aureus ATCC 6538 at concentration 40% b/v, 60% b/v, 80% b/v but ineffective against Escherichia coli ATCC 11229 bacteria in vitro.